Fluctuation of Insect Population on Rice Field in Pangkalan Sub-district Karawang Regency: Indicator for Environmental Health - Afifah, Lutfi; Sugiono, Darso (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
Pangkalan Sub-district is a forest edge area in Karawang that is rich in flora and fauna that has not been much identified. Because of its unique location that is bordered by primary forest, agricultural ecosystems in the area will not be separated from the influence of the surrounding forest. So, it is necessary to know more about the diversity and abundance of insects in the wetland rice ecosystems.The research was conducted in Pangkalan sub-district, Karawang regency. The size of each plot was 5 x 5 m (25 m2) and each treatment was repeated five times. Treatments carried out with integrated pest management (IPM), chemical pest management techniques (P-K), and Mixed Pest Management (P-C). Insect retrieval technique using sweep net method, yellow pan trap, and direct observation. The abundance of arthropod species found in 12 Orders consist of: Thysanoptera Order (2.4%), Orthoptera (0.5%), Odonata (1.4%), Mantodea (0%), Lepidoptera (8.7%), Hymenoptera (2.4%), Hemiptera (61.8%), Diptera (2.4%), Derma ptera (3.6%), Coleoptera (8.3%), Architaenioglossa (0.5%), and Aranea (8.0%). Based on the species richness, it was found that the orders of Diptera (25 species), Coleoptera (19 species), and Hymenoptera (18 species) showed higher numbers than other orders. The H 'diversity index in this study ranged from 1.99 to 2.45, the D index ranged from 0.73 to 0.88, and the E index ranged from 0.5 to 0.7. Overall the P-K plots showed a lower population abundance compared to IPM and P-C plots. Intense and scheduled spraying of insecticides on P-K plots causes a lower population abundance, which makes the diversity become low. Keywords: Rice pests, diversity of insects, natural enemies, pesticides, integrated pest control (IPM)